1976
DOI: 10.1103/physrevc.13.2182
|View full text |Cite
|
Sign up to set email alerts
|

Ge70high-spin levels via theZn

Abstract: The nucleusGe has been studied via the +Zn{n, 2ny) Ge reaction at E~= 30 MeV using different in-beam y spectroscopic techniques. Levels up to 5.5 MeV have been identified and spins up to 8+ have been established.NUCLEAR REACTIONS +Zn{n, 2ny) E~= 30 MeV, yy coincidences, angular distributions, level scheme deduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
28
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 12 publications
9
28
0
1
Order By: Relevance
“…The ground state positive-parity band determined from the present work is shown in Fig.1 as band B1. This band was known previously up to spin, J π = (12 + ) [12,15,24] and is extended to 14 in the present work with inclusion of 1051 keV γ-ray transition on top of 12 + level. An example of γ-γ coincidence spectrum gated on 906 keV is shown in Fig.…”
Section: Highsupporting
confidence: 61%
See 1 more Smart Citation
“…The ground state positive-parity band determined from the present work is shown in Fig.1 as band B1. This band was known previously up to spin, J π = (12 + ) [12,15,24] and is extended to 14 in the present work with inclusion of 1051 keV γ-ray transition on top of 12 + level. An example of γ-γ coincidence spectrum gated on 906 keV is shown in Fig.…”
Section: Highsupporting
confidence: 61%
“…Low-spin states of 70 Ge were previously investigated through the (p, p ′ ), (n, n ′ γ), (p,t) and ( 3 He, d) reactions [10][11][12][13]. These studies reported the level structure of 70 Ge up to 5.1 MeV excitation energy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the 199/2-2P3/2 proton splitting (1 972 keV in 69Ga [13]) and the small 199/2-2pl/2 neutron splitting (198 keV in ' 1 Ge [14]) enables us to build high spin states up to 9 + . As a support we may note the work of C. C. Lu et al [15] 68Zn(a, 2ny)'°Ge which was used in our study of 7 'Ge [17] and 68Zn(a, pn7)7'Ga with a cross section (estimated by means of the y transitions to the G.S.) which is 10 times smaller than that of the (a, 2n) reaction.…”
supporting
confidence: 60%
“…which is 10 times smaller than that of the (a, 2n) reaction. We shall only describe here the experimental set-up specific to the 7OGa study and ask the reader to refer to the7OGe paper [17] for any further information.…”
mentioning
confidence: 99%
See 1 more Smart Citation